Pengembangan Mutu Pendidikan Di Negara Berkembang - Zainal Panani; Asy’aril Muhajir; Nur Effendi (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of writing this article is to determine the development of education quality in developing countries. This research uses a type of library research. Library research is research carried out by reviewing various journals and related reference books. The results of his research show that quality education is education that can produce students who have abilities, insight and skills in accordance with established standards, so that they have sufficient opportunities to be competent in any job market without ignoring the moral aspects of their lives. A developing country is a country with a low average income, relatively underdeveloped infrastructure, and a human development index that is poor compared to global norms. Educational policies in developing countries generally originate from the legacy of colonial educational policies. It is said this because developing countries when they first became independent had not yet developed their own educational policies based on the realistic needs of their people. The independence that has been achieved in the political field is not automatically followed by independence in other fields, especially in the field of education. The causes of the low quality of education in developing countries are, 1) lack of qualified teachers, 2) failure of schools to care for students, in fact elementary schools are less effective in supporting the development movement, if the impact is not proven within an appropriate period of time, 3) poor state of the curriculum. not appropriate. The basic problems of the curriculum at the pre-university level include the expansion of cultural adaptation, localization and vocationalization of the curriculum, 4) Inequality in rural and urban progress.